Asymmetrical‐Dendronized TADF Emitters for Efficient Non‐doped Solution‐Processed OLEDs by Eliminating Degenerate Excited States and Creating Solely Thermal Equilibrium Routes. (20th January 2022) - Li, Chensen; Harrison, Alastair K.; Liu, Yuchao; Zhao, Zhennan; Zeng, Cheng; Dias, Fernando B.; Ren, Zhongjie; Yan, Shouke; Bryce, Martin R.
Abstract: The mechanism of thermally activated delayed fluorescence (TADF) in dendrimers is not clear. We report that fully‐conjugated or fully‐nonconjugated structures cause unwanted degenerate excited states due to multiple identical dendrons, which limit their TADF efficiency. We have synthesized asymmetrical "half‐dendronized" and "half‐dendronized‐half‐encapsulated" emitters. By eliminating degenerate excited states, the triplet locally excited state is ≥0.3 eV above the lowest triplet charge‐transfer state, assuring a solely thermal equilibrium route for an effective spin‐flip process. The isolated encapsulating tricarbazole unit can protect the TADF unit, reducing nonradiative decay and enhancing TADF performance. Non‐doped solution‐processed devices reach a high external quantum efficiency (EQEmax ) of 24.0 % (65.9 cd A −1, 59.2 lm W −1 ) with CIE coordinates of (0.24, 0.45) with a low efficiency roll‐off and EQEs of 23.6 % and 21.3 % at 100 and 500 cd m −2 . Abstract : Two asymmetric "half‐dendronized" and "half‐dendronized‐half‐encapsulated" TADF emitters eliminate degenerate excited states, assuring a solely thermal equilibrium route for an effective spin‐flip process. AEE properties can minimize the exciton quenching. The isolated encapsulating tricarbazole unit protects the TADF unit, reducing nonradiative decay. Non‐doped OLEDs with a remarkably high EQEmax of 24.0 % and low roll‐off are achieved.